2017
DOI: 10.1002/ep.12745
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and isotherm studies on acid dye adsorption using thermal and chemical activated Jatropha husk carbons

Abstract: Activated carbon was prepared from Jatropha husk, as a biodiesel byproduct waste, by physical (JHC) and chemical (ZnCl2) activation (ZAJHC), as an adsorbent for the removal of acid dye Acid blue 83 (AB83). Batch adsorption experiments were carried out to study the effects of various physicochemical parameters such as contact time, initial dye concentration, adsorbent dose, and initial solution pH. The AB83 loaded and unloaded adsorbent materials were characterized by SEM, EDX, XRD, and FTIR. Lagergren first‐or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…As the temperature decreased, the Gibbs free energies also decreased, which indicated that the adsorption process was effective at high temperatures, namely, increasing the temperature was conducive to the adsorption process. Additionally, according to the literature, physical, physico-chemical, and chemical adsorption processes occurred at −20~0, −20~−80, and −80~−400 kJ/mol, respectively [31]. Therefore, according to the calculated Gibbs free energy, the adsorption types of NH 2 -SH-GO/ o-MWCNTs for lead ions and phenol can be judged.…”
Section: Adsorption Thermodynamicsmentioning
confidence: 98%
“…As the temperature decreased, the Gibbs free energies also decreased, which indicated that the adsorption process was effective at high temperatures, namely, increasing the temperature was conducive to the adsorption process. Additionally, according to the literature, physical, physico-chemical, and chemical adsorption processes occurred at −20~0, −20~−80, and −80~−400 kJ/mol, respectively [31]. Therefore, according to the calculated Gibbs free energy, the adsorption types of NH 2 -SH-GO/ o-MWCNTs for lead ions and phenol can be judged.…”
Section: Adsorption Thermodynamicsmentioning
confidence: 98%
“…It is the raw material in the production of polymeric dyes and, as a derivative of the two ringed PAH, represents the main component of toxic and recalcitrant organic pollutants (Hadibarata et al, 2012). Acid Blue 83 (AB 83) is commonly used in the textile industry, but recent studies emphasized the carcinogenic and mutagenic properties of this dye (Karthick et al, 2018).…”
Section: Introductionmentioning
confidence: 99%